The Harmony Of Individualism And Collectivism In Pancasila Democracy - Junaedi Junaedi (PT Publikasiku Academic Solution, 2024)
Indonesia, as a country with the Pancasila philosophy, has values that include individualism and collectivism. However, in practice, there is sometimes a misalignment between the concepts of individualism and collectivism in the implementation of Pancasila democracy. This study aims to identify and analyze the alignment between the concepts of individualism and collectivism in the context of Pancasila democracy. This research uses qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that Pancasila democracy is an ideal government system to balance individualism and collectivism. Individualism and collectivism can be harmonized in Pancasila democracy by implementing several strategies, including strengthening character education to instill Pancasila values, increasing community participation in the democratic process, and empowering communities through sustainable development programs.